Gender issues and management performance - Bacalso, Ivy Lourdes; Pastor, Joan Michelle P.; Pastrana, Ruby Ann.; Pinuela, Rhea Joy T.; Tejida, Loraine Mei C. (2005.)
This study aimed at determining whether gender issues influence management performance. It emphasizes the need to address the different gender-related issues in the workplace in order to increase the effectiveness of the employees and the management in carrying out the organization's goals. Most of today's organizations have surpassed the requirements of equal opportunities in employment. They recognize the importance of focusing on the management of a diverse workforce as a survival imperative. However, in any organization, the success and failure are being attributed to the manager. With these, we seek to know the effects or impact of having a male or a female manager and if differences really exist in the way they run and manage the organization. Most importantly, we seek to know if the gender of a manager is of importance to the success of the organization in which he or she belongs. We are all aware of the continued battle for gender equality and disparity in employment. Much has, therefore, been aired regarding the management of workforce, diversity of granting equal employment, with the management being advised to tend to their legal obligations towards diversity and the socio-political and economic implications of mismanagement. Data were gathered at random from employees of several financial institutions using a 13-item questionnaire. The questions posed by the latter are basically catigorized into three such as career competence, work roles of men and women and work behavior.
Research Paper (Mgt 199-Management Research). [Iloilo City : University of the Philippines Visayas -College of Management], March 2005.